1994
DOI: 10.3327/jnst.31.1073
|View full text |Cite
|
Sign up to set email alerts
|

Separation Technology for Radioactive Iodine from Off-Gas Streams of Nuclear Facilities.

Abstract: Iodine separation technology using an inorganic adsorption material has been investigated in order to apply the technology to the off-gas treatment systems of nuclear facilities. Iodine removal efficiencies were checked by laboratory experiments using simulated off-gas streams of various conditions and the developed adsorbent, silver impregnated alumina (AgA). Laboratory test results demonstrated effective iodine removal with high decontamination factors (DF's) a t relatively high temperatures ( 2 100°C). Then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…Caustic scrubbing may avoid this equipment pitfall with acceptable DFs, but the alkaline solutions tend to absorb CO 2 over time, decreasing the effectiveness of the method, and also may not effectively remove organic iodides [27]. Thus, high amounts of solvent must be used to combat this and retain an acceptable DF [12].…”
Section: Capture Of Radioactive Contaminants By Wet Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…Caustic scrubbing may avoid this equipment pitfall with acceptable DFs, but the alkaline solutions tend to absorb CO 2 over time, decreasing the effectiveness of the method, and also may not effectively remove organic iodides [27]. Thus, high amounts of solvent must be used to combat this and retain an acceptable DF [12].…”
Section: Capture Of Radioactive Contaminants By Wet Processesmentioning
confidence: 99%
“…AgNO 3 reacted with elemental iodine to form the stable silver iodide/iodate. Fukasawa et al [12,45] developed a silver nitrate impregnated alumina sorbent (24% AgA). The capacity of sorbent was investigated for capture of iodine from a reprocessing plant using continuous column at a velocity of 20 cm s -1 at 423 K. They concluded that parameters (iodine concentration, gas flow rate) other than temperature had no effect on decontamination factor (DF's).…”
Section: Sorbents For Capture Of Radioactive Volatile Iodinementioning
confidence: 99%
See 1 more Smart Citation
“…6 indicate almost no iodine release for AgA after heating to 450C. As I 2 is known to adsorb as forms of insoluble AgI and soluble AgIO 3 and AgIO 3 changes to AgI by heating, AgA with heat treatment drastically reduces the iodine release to water (9) . Thus AgA is found to be also suitable for storage and disposal after use.…”
Section: Fig 5 View Of Aga and Agsmentioning
confidence: 99%
“…In recent years, adsorption onto a porous adsorbent has been the primary choice for the removal of radioactive iodine gas due to its advantages that include reliability, simplicity and low operating costs [7]. Previously, several sorbents has been investigated to trap the iodine which includes activated carbon [8,9], silver-exchange zeolite [10], AgNO 3 -impregnated silica and alumina [11,12], silver-functionalized silica aerogels [13], silver-exchanged titania (ETS-10) [14], chalcogen-based aerogel [15][16][17][18], monolithic aerogels of polymeric organic framework [19], and metal organic frameworks [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%